2022
DOI: 10.3389/fphys.2022.807632
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas—Its Functions, Disorders, and Physiological Impact on the Mammals’ Organism

Abstract: This review aimed to analyze the scientific literature on pancreatic diseases (especially exocrine pancreatic insufficiency). This review also describes the correlation between the physiological fitness of the pancreas and obesity. The influence of the pancreatic exocrine function on the development of the organism of adults and adolescents was also described. The results of piglet studies available in the literature were cited as an established model used to optimize treatments for pancreatic diseases in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 70 publications
0
39
0
1
Order By: Relevance
“…This fibrosis was noted to extend toward the proximal duodenal portion to involve the sphincter of Oddi, thus contributing to the loss of digestive excretions of the pancreaticobiliary system as excretions were unable to enter the enteric tract. A lack of enzymatic activity in the enteric tract including pancreatic lipase, amylase, and protease likely led to his subsequent weight loss and diarrhea symptoms as these enzymes are key for the digestion of fats, starches, and sugars, respectively [ 7 ]. This scenario is supported by the measured deficiency in pancreatic lipase in the patient’s stool sample early during his hospital course.…”
Section: Discussionmentioning
confidence: 99%
“…This fibrosis was noted to extend toward the proximal duodenal portion to involve the sphincter of Oddi, thus contributing to the loss of digestive excretions of the pancreaticobiliary system as excretions were unable to enter the enteric tract. A lack of enzymatic activity in the enteric tract including pancreatic lipase, amylase, and protease likely led to his subsequent weight loss and diarrhea symptoms as these enzymes are key for the digestion of fats, starches, and sugars, respectively [ 7 ]. This scenario is supported by the measured deficiency in pancreatic lipase in the patient’s stool sample early during his hospital course.…”
Section: Discussionmentioning
confidence: 99%
“…Disorders of the pancreas affect the ability of this organ to biosynthesise and/or secrete sufficient enzymes to digest food in the intestines. 30 Disorders that affect pancreatic function include chronic/acute pancreatitis, neoplastic disease, hereditary diseases (e.g., cystic fibrosis), diabetes, and Shwachman-Diamond syndrome. 30 Accumulating research has shown an association between microbiome abnormalities and pancreatic disease, but it is not yet clear whether microbial dysbiosis is a cause or an effect of pancreatic dysfunction.…”
Section: Disorders Of the Pancreasmentioning
confidence: 99%
“…Fruit bats demonstrate high sensitivity to glucose and insulin ( 19 ) and can directly fuel their metabolic needs with exogenous sugars ( 25 ). The pancreas is responsible for generating hormones that regulate blood sugar and appetite, such as insulin and glucagon ( 26 ), as well as secreting enzymes and digestive juices into the small intestine ( 27 ). The high sensitivity to sugar levels in fruit bats is thought to be supported by an expansion of endocrine tissue in the pancreas ( 18, 19 ) and by loss of genes involved in insulin metabolism and signaling ( 20 ).…”
Section: Introductionmentioning
confidence: 99%